Síntese e caracterização de aluminofosfato impregnado com molibdênio/zinco visando a dessulfurização por adsorção - Gomes, Kalyanne Keyly Pereira (2011)
Discussions about pollution caused by vehicles emission are old and have been developed along the years. The search for cleaner technologies and frequent weather alterations have been inducing industries and government organizations to impose limits much more rigorous to the contaminant content in fuels, which have an direct impact in atmospheric emissions. Nowadays, the quality of fuels, in relation to the sulfur content, is carried out through the process of hydrodesulfurization. Adsorption processes also represent an interesting alternative route to the removal of sulfur content. Both processes are simpler and operate to atmospheric temperatures and pressures. This work studies the synthesis and characterization of aluminophosphate impregnate with zinc, molybdenum or both, and its application in the sulfur removal from the gasoline through the adsorption process, using a pattern gasoline containing isooctane and thiophene. The adsorbents were characterized by x-ray diffraction, differential thermal analysis (DTG), x-ray fluorescence and scanning electron microscopy (SEM). The specific area, volume and pore diameter were determined by BET (Brunauer- Emmet-Teller) and the t-plot method. The sulfur was quantified by elementary analysis using ANTEK 9000 NS. The adsorption process was evaluated as function of the temperature variation and initial sulfur content through the adsorption isotherm and its thermodynamic parameters. The parameters of entropy (ΔS), enthalpy variation (ΔH) and free Gibbs energy (ΔG) were calculated through the graph ln(Kd) versus 1/T. Langmuir, Freundlich and Langmuir-Freundlich models were adjusted to the experimental data, and the last one had presented better results. The thermodynamic tests were accomplished in different temperatures, such as 30, 40 and 50ºC, where it was concluded the adsorption process is spontaneous and exothermic. The kinetic of adsorption was studied by 24 h and it showed that the capability adsorption to the adsorbents studied respect the following order: MoZnPO > MoPO > ZnPO > AlPO. The maximum adsorption capacity was 4.91 mg/g for MoZnPO with an adsorption efficiency of 49%.